Mercedes Inés Carazo: Science, Technology, and Innovation: A Local Agenda - Vásquez Rodríguez, Rafael (2026)
Public policies on science, technology, and innovation are often evaluated based on their funding, infrastructure, or the number of projects they support. However, there is another fundamental criterion that frequently goes unnoticed: user satisfaction—that is, the satisfaction of the researchers, entrepreneurs, producers, and citizens who are supposed to benefit from these policies. To reflect on this topic, we spoke with Mercedes Inés Carazo, a physicist by training, an innovation manager, and one of the most influential figures in the promotion of technology ecosystems in Peru. Carazo has been a driving force behind technology incubators, a promoter of technology management programs, and the executive director of the Peruvian Technology Platform. Her career combines academia, public administration, and work with entrepreneurs.